Efektifitas Edukasi aplikasi online Berbasis android terhadap suami ibu hamil tentang ASI eksklusif - Putriana, Yeyen; Pranajaya, R; Mujab, Saiful (MIDWIFERY JOURNAL, 2023)
Background: The failure of exclusive breastfeeding is mostly caused by the mother’s lack of knowledge and the absence of family support, especially husbands and in-laws or birth mothers. So far, pregnant women who visit health centers and midwives who practice independently have received education about exclusive breastfeeding through the KIA book media. However, family knowledge, especially husbands, have not received the same understanding of exclusive breastfeeding. Online applications about exclusive breastfeeding have been widely circulated in the community. However, it is not yet known how the effectiveness of this online application on the knowledge of the husband of pregnant women. Purpose :The research objective was to know the differences in knowledge and attitudes of husbands of pregnant women towards exclusive breastfeeding before and after using online media applications based on android.Method:The study used a quasi-experimental research design. The activity was carried out at the Kemiling Bandar Lampung puskesmas. The research subjects were husbands of pregnant women. The sample size used a purposive sampling formula of 30 respondents according to the inclusion criteria of the study. Data analysis used univariate and bivariate analysis using paired T test. The android based application is designed by the researcher. With the name sipenyu. The web network used is the Poltekkes Tanjungkarang web and can be downloaded from the play store. Conclusion: The results showed that there was an increase in the knowledge and attitudes of the husbands of pregnant women towards exclusive breastfeeding with p = 0.000. before and after the appSuggestion : the use of the Sipenyu application can be used to increase the knowledge and attitude of pregnant husbands towards exclusive breastfeeding Key words: apliction, online, android, husband, pregnant women, eclusiv berastfeeding AbstrakLatar Belakang :Kegagalan ASI ekslusif banyak disebabkan oleh kurangnya pengetahuan ibu dan tidak ada adanya dukungan keluarga terutama suami dan mertua atau ibu kandung . Selama ini ibu hamil yang berkunjung ke puskesmas dan bidan praktik mandiri telah mendapatkan edukasi tentang ASI ekslusif melalui media buku KIA. Namun pengetahuan keluarga terutama suami  belum mendapatkan pengertian yang sama tentang ASI ekslusif. Aplikasi online tentang ASI esklusif telah banyak beredar di masyarakat. Namun belum diketahui bagaimanakan efektitas aplikasi online tersebut terhadap pengetahuan  suami ibu hamil.Tujuan penelitian diketahuniya perbedaan pengetahuan dan sikap suami  ibu hamil terhadap ASI ekslusif sebelum dan sesudah  menggunakan media aplikasi online berbasis android.Metode :Penelitian menggunakan rancangan enelitian quasi eksperimen  . Kegiatan   dilaksanakan di puskesmas Kemiling Bandar Lampung. Subyek penelitian adalah suami ibu hamil . Besar sampel menggunakan rumus purposive sampling sebanyak 30 reponden yang sesuai dengan kriteria inklusi penelitian  . Analisa data menggunakan analisa univariate dan bivariate dengan menggunakan uji T paired. Aplikasi berbasis android dirancang sendiri oleh peneliti. Dengan nama sipenyu. Jaringan web yang digunakan adalah web poltekkes Tanjungkarang dan dapat diunduh di play store. Hasil: penelitian didapatkan terdapat peningkatan pengetahuan dan sikap suami ibu hamil terhadap asi eklsusif dengan p= 0.000. sebelum dan sesudah diberikan aplikasi.Saran : penggunaan aplikasi sipenyu  dapat digunakan untuk meningkatkan pengetahuan dan sikaf suami hamil terhadap asi eklusifKata Kunci : aplikasi, online, android, suami, ibu hamil, asi ekslusif.